2014
DOI: 10.14814/phy2.12083
|View full text |Cite
|
Sign up to set email alerts
|

The obesity-associated gene Negr1 regulates aspects of energy balance in rat hypothalamic areas

Abstract: Neural growth regulator 1 (Negr1) is among the first common variants that have been associated with the regulation of body mass index. Using AAV technology directed to manipulate Negr1 expression in vivo, we find that decreased expression of Negr1 in periventricular hypothalamic areas leads to increases in body weight, presumably via increased food intake. Moreover, we observed that both increased and decreased levels of Negr1 lead to reduced locomotor activity and body temperature. In sum, our results provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…Previous research has identified this gene as a possible 468 susceptibility gene for obesity (Yanagiya et al 2007); however, relatively little is known about any 469 functional consequences of SNPs within this pseudogene. We also observed a strongly associated locus 470 in NEGR1, one of the first genes shown to have variants associated to BMI (Thorleifsson et al 2008;471 Willer et al 2009;Speliotes et al 2010;Boender et al 2014). This gene codes for a cell adhesion 472 molecule, although its function in relation to BMI is still unknown.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Previous research has identified this gene as a possible 468 susceptibility gene for obesity (Yanagiya et al 2007); however, relatively little is known about any 469 functional consequences of SNPs within this pseudogene. We also observed a strongly associated locus 470 in NEGR1, one of the first genes shown to have variants associated to BMI (Thorleifsson et al 2008;471 Willer et al 2009;Speliotes et al 2010;Boender et al 2014). This gene codes for a cell adhesion 472 molecule, although its function in relation to BMI is still unknown.…”
supporting
confidence: 62%
“…Furthermore, 77% of the SNPs in this second GWAS (21/27) were previously associated 306 with BMI in previous research studies (Scuteri et al 2007;Frayling et al 2007;Dina et al 2007;307 Zeggini et al 2007;Yanagiya et al 2007;Hinney et al 2007;Hunt et al 2008;Price et al 2008;Grant 308 et al 2008;Hotta et al 2008;Loos et al 2008;Tan et al 2008;Villalobos-Comparán et al 2008;309 Thorleifsson et al 2008;Willer et al 2009;Meyre et al 2009;Wing et al 2009;Liu et al 2009;310 Shimaoka et al 2010;Fawcett and Barroso 2010;Speliotes et al 2010;Wang et al 2011;Prakash et 311 al. 2011;Okada et al 2012;Cha et al 2012;Berndt et al 2013;Wheeler et al 2013;Graff et al 2013;312 Olza et al 2013;Boender et al 2014;Christensen et al 2015;Nakajima et al 2016;Thomsen et al 313 2016;Qureshi et al 2017;Huđek et al 2018;Gonzalez-Herrera et al 2018). With the addition of DM2 314 as a covariate, the GWAS identified several additional SNPs on chromosome 8, as well as SNPs on 315 chromosomes 17 and 19.…”
Section: Gwas Of Bmi In the Healthy Nevada Cohort 266mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an association between NEGR1 and obesity has been reported by Wheeler et al [2013] and Boender et al [2014]. These authors found that decreased expression of NEGR1 in periventricular hypothalamic areas of rats led to an increase in body weight, presumably via increased food intake.…”
Section: Discussionmentioning
confidence: 79%
“…As Kilon is found chiefly at axons and presynaptic terminals, it can be mainly expressed at the dendritic postsynaptic spine of neurons [Alvarez and Sabatini, 2007]. NEGR1 has become of great interest based on the recent findings that its genetic alteration is implicated in human obesity and human dyslexia [Willer et al, 2009;Veerappa et al, 2013;Wheeler et al, 2013;Boender et al, 2014]. As NEGR1 is involved in neurite outgrowth [Schäfer et al, 2005], a process known to be involved in human obesity [Farooqi and O'Rahilly, 2007], these observations could form the basis for a molecular explanation for this association, which needs to be experimentally tested.…”
Section: Discussionmentioning
confidence: 99%